New frontiers in research on industrial decarbonization - Gillingham, Kenneth T; Barrage, Lint; Armitage, Sarah; Burtraw, Dallas; Colmer, Jonathan; de Preux, Laure; Hawkins-Pierot, Jonathan; Holt, Charles; Karplus, Valerie J; Löfgren, Åsa; Martin, Ralf; Miller, Nathan; et al. (Science (American Association for the Advancement of Science), 2025)
Research is needed to quantify impacts and understand interactions with the broader economy.